Incidence of Dermatitis in Urban Communities: A Study in Tallo Village, Makassar City - Dewi, Chitra; Syam, Ilham; Syahrir, Muhammad; Sahida, Muti; Sarkol, Martha Celsi (Universitas Mandala Waluya, 2025)
Dermatitis is a skin inflammation that is often considered trivial but has a high prevalence in Indonesia. In Makassar, 97,331 cases were recorded in 2012 and 2,030 cases (15.63%) in Rappokalling Health Centre in 2015. Personal hygiene and environmental sanitation factors contribute to this incidence. The study aimed to describe the incidence of dermatitis in Tallo Village, especially RT 01/RW 04. The study used a descriptive design; the population was all people in RT 01 RW. 04 Tallo Village, Tallo District, Makassar City, as many as 321 people and a sample of 178 respondents were selected by accidental sampling. Data were collected through questionnaires and observation and analyzed univariately. The results showed 95 respondents (53.4%) suffered from dermatitis. One hundred sixty-nine respondents (94.9%) had good personal hygiene behavior, but the cleanliness of towels (44.9%) and bed/bed linen (27%) was still low. All respondents used clean water that met the requirements but did not have proper waste disposal facilities. The conclusion of this riset are incomplete personal hygiene, poor environmental sanitation, and waste management contributed to the high number of dermatitis cases. Routine education on personal hygiene and the provision and supervision of proper waste disposal facilities by the government and health centers are recommended to prevent dermatitis in the community.